Sistem Pakar Diagnosis Penyakit Gagal Jantung Kongestif, Penyakit Paru Obstruktif Kronik, Dan Asma Berdasarkan Gejala Utama Sesak Kronik Menggunakan Kombinasi Metode K-Nearest Neighbor Dan Certainty Factor - Jeffrey Junior Tedjasulaksana; Imam Cholissodin; Indriati Indriati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Health is very important for everyone's life and if it is not cured immediately, it can interfere with activities so it can cause death. According to several studies, one of the diseases that is often experienced by everyone is a disease with symptoms of shortness of breath or difficulty breathing. Chronic shortness is most often caused by heart diseases such as congestive heart failure or respiratory disease, asthma and chronic obstructive pulmonary disease (COPD). Several studies reported that the compatibility between a diagnosis by a general practitioner in primary health care and a final diagnosis by a specialist is only less than 50%. So in this study an expert system was made to diagnose congestive heart disease (CHF), chronic obstructive pulmonary disease (COPD), and asthma using a combination of the K-Nearest Neighbor method to classify diseases with the Certainty Factor method to determine the level of confidence from the previous classification results using 20 symptoms. The data used is patient data at Jumpandang Baru Public Health Center in Makassar City with a total of 100 data. The best accuracy results in testing variations in the K value are 100% when the K value is 3 and the results of testing the comparison of accuracy when using a combination of the K-Nearest Neighbor - Certainty Factor method and when only using the K-Nearest Neighbor method it produces the same accuracy value.